Confirmatory factor analysis (CFA) untuk validasi instrumen sexual bullying questionarry (SEBUQU) - Bariyyah, Khairul; Pratama, Aji Mulya; Tsaqofah, Anis; Pratiwi, Nabila Pujias; Siwi, Raras Amalia Cantika; Ahfadzi, Yuniar Fitri; Budiyono, Alief Laili; Maizura, Nining (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The Sexual Bullying Questionnaire (SeBuQu) is an instrument developed to assess students' understanding of sexual violence at SMPN 30 Malang. This study aims to develop a valid and reliable sexual bullying questionnaire instrument using Confirmatory Factor Analysis (CFA). The objective is for the validated instrument (SeBuQu) to be usable by counselors to assess students' understanding of sexual bullying in schools. The method used to validate this instrument is Confirmatory Factor Analysis. The results of this study indicate that all questionnaire items significantly contribute to the measured construct, understanding sexual bullying, as confirmed through CFA. The analysis shows that this instrument has a good goodness-of-fit, indicating that the proposed model is valid. Through the use of this instrument, it is hoped that counselors can take a more proactive role in educating students about sexual violence, fostering a safer school environment, and reducing incidents of sexual bullying among adolescents. Future research could focus on adapting and applying this instrument in different school contexts and exploring factors that influence students' understanding of sexual violence.